Strategic Planning Challenges Faced by Clothing Retail SMEs in Cape Town, South Africa - Sobende, Xolela; Herbst, Frederick J.; Twum-Darko, Michael; Noruwana, Nimrod (Reshaping Sustainable Development Goals Implementation in the World: Proceeding of 7th International Conference on Business and Management Dynamics, 2021)
The objective of this study was to investigate the challenges faced by SMEs in relation to strategic planning in the clothing retail industry in Cape Town. A mixed method consisting of both qualitative and quantitative questions was adopted. A survey questionnaire including in-depth questions as well as open-ended questions was used. A descriptive research design was used which aimed to describe the problem as it exists. Convenience sampling was used which yielded 56 participants comprising clothing retail owners. Clothing retailers faced a variety of strategic planning challenges. These challenges include the non-communication of strategic planning to all levels of the business, not prioritizing strategic planning, neglecting strategic planning, and poor strategic plans. Government regulations, industry competition and lack of management skills are the key factors that have an impact on the strategic planning process. The findings reveal that managers and owners have been confusing strategic planning and strategy implementation which has implications for the strategic planning process.